Touching creativity; a review and early pilot test of haptic tooling to support design practice, within a distance learning curriculum. (2nd January 2019) - Bowers, Lisa Jane
ABSTRACT: Machine haptics has been shown to assist and enhance human–computer interactions. Research from previous studies in the field of haptics has focused on developing a user's sense of realism of touch when using a haptic device. This paper examines the use of haptics for education, specifically for creative online education. The paper is presented in two parts. First, a review of literature was conducted and used to aid the rationale and underpin the design of a pilot test. Second, a pilot test was designed using a single-point kinaesthetic haptic device with a haptic rendered interface, to support the assembly of a virtual design prototype. The pilot test proved to be extremely valuable in creating and developing a rich virtual environment for non-sighted and sighted participants to use. The results from the initial pilot test showed that although users were positive about their experience of using the haptic device, there were improvements to be made to the interface to enhance the user experience in the next phase of testing.